Sources of Error in Interventional Radiology: How, Why, and When. Issue 4 (November 2020) - Mafeld, Sebastian; Oreopoulos, George; Musing, E. L. S.; Chan, Tze; Jaberi, Arash; Rajan, Dheeraj
This article aims to provide an overview of the sources for error in interventional radiology (IR). Being both a procedure and an imaging-based specialty, IR has unique considerations as to how error can occur. However, compared to the surgical and medical literature, data on error in IR are lacking. The available IR literature is reviewed but supplemented with lessons from other specialties and the World Health Organization. Individual risks such as cognitive bias as well as system-level factors are also considered in order to generate a taxonomy for error in IR that includes the operator, patient, team, and environment.